Social Comparisons and Pro-social Behavior: Testing “Conditional Cooperation” in a Field Experiment - Frey, Bruno S; Meier, Stephan (American Economic Review, 2004)
Social Comparisons and Pro-social Behavior: Testing "Conditional Cooperation" in a Field Experiment by Bruno S. Frey and Stephan Meier. Published in volume 94, issue 5, pages 1717-1722 of American Economic Review, December 2004